Hubungan Program Persiapan Asi Prenatal Di Kih Pada Ibu Hamil Trimester 3 dengan Breastfeeding Self Efficacy Ibu di PMB Risma Sitepu Kota Bekasi Tahun 2025 - Khairiah, Rahayu; Samosir, Delima (Jurnal Ners, 2025)
Exclusive breastfeeding can save the life of a baby until he/she becomes an adult. Proper breastfeeding has many benefits for both mother and baby. Exclusive breastfeeding preparation or lactation management is an effort made by mothers and families to support successful breastfeeding. The success of mothers in providing exclusive breastfeeding is supported by a factor of self-confidence (breastfeeding self-efficacy). Breastfeeding self-efficacy is a basic thing that mothers have to breastfeed which includes the efforts and ways of mothers to overcome problems found during breastfeeding. To find out the Relationship between the Prenatal Breastfeeding Preparation Program at KIH for pregnant women in the 3rd trimester with the Breastfeeding self-efficacy of mothers at PMB Risma Sitepu, Bekasi City in 2025. This study uses a quantitative research design using an analytical survey method with a cross-sectional approach. Based on the results of the study, there is a relationship between Prenatal Breastfeeding preparation regarding mothers’ knowledge of breast anatomy and breast care at KIH for pregnant women in the 3rd trimester with the Breastfeeding self-efficacy of mothers with a p-value of 0.000 (<0.05). relationship between Prenatal Breastfeeding preparation and maternal knowledge about Nutrition during breastfeeding at KIH in pregnant women in the third trimester with Breastfeeding self-efficacy of mothers with a p-value of 0.003 (<0.05) and There is a relationship between the economic status of pregnant women in the third trimester with Breastfeeding self-efficacy of mothers with a p-value of 0.001 (<0.05). There is a Relationship between the Prenatal Breastfeeding preparation program at KIH in pregnant women in the third trimester with Breastfeeding self-efficacy of mothers at PMB Risma Sitepu, Bekasi City in 2025